(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Alzheimer’s, accounting for 60-80% of dementia cases, presents a specific pathology and a range of symptoms, including memory loss, impaired reasoning, and other cognitive declines. The disease’s progression and management require a comprehensive approach involving professional care, family involvement, and individualized care plans. The research focuses on methods for working with individuals with Alzheimer’s disease and their families, highlighting the importance of communication in implementing individualized care plans. It aims to show that a well-prepared care plan, coupled with effective communication with family members, can improve quality of life and potentially slow disease progression. It was conducted in two parts: a questionnaire for caregivers working with Alzheimer’s patients and a semi-structured interview with 33 family members of individuals diagnosed with the disease. This approach provided both quantitative and qualitative data, offering a comprehensive understanding of the issues. To improve Alzheimer’s care, we recommend enhancing family involvement through structured models and training, increasing the accessibility of specialized services, promoting professional development, strengthening ethical communication standards, implementing comprehensive support systems, and regularly evaluating care plans. These measures aim to provide holistic and effective care strategies, improving the quality of life for individuals with Alzheimer’s and their families.